Guinea-Bissau : 2022 Article IV Consultation and Third Review under the Staff-Monitored Program; Press Release; and Statement by the Executive Director for Guinea-Bissau. (IMF Staff Country Reports; Country Report ;, 2022)
After years of political turmoil and delayed reforms, the authorities started implementing in 2021 an ambitious fiscal consolidation and reform program to ensure debt sustainability, create fiscal space to address developmental needs and strengthen state capacity. A Rapid Credit Facility (RCF) disbursement of SDR 14.2 million (50 percent of quota) was approved in January 2021 to provide urgent financing to support critical spending in health. A 9-month Staff-Monitored Program (SMP) with three quarterly reviews was approved in July 2021 to support the government's reform program aimed at stabilizing the economy, strengthening governance, and building track record of policy implementation to underpin the authorities' request for an Extended Credit Facility (ECF) arrangement. The August 2021 SDR 27.2 million allocation and the reforms underpinned by the SMP have helped address the adverse impact of the pandemic, improve government spending transparency, mitigate debt vulnerabilities.